Flexible thin-film acoustic wave devices with off-axis bending characteristics for multisensing applications - Zhangbin Ji (Nature Publishing Group, 2021)
Abstract Flexible surface acoustic wave (SAW) devices have recently attracted tremendous attention for their widespread application in sensing and microfluidics. However, for these applications, SAW devices often need to be bent into off-axis deformations between the acoustic wave propagation direction and bending direction. Currently, there are few studies on this topic, and the bending mechanisms during off-axis bending deformations have remained unexplored for multisensing applications. Herein, we fabricated aluminum nitride (AlN) flexible SAW devices by using high-quality AlN films deposited on flexible glass substrates and systematically investigated their complex deformation behaviors. A theoretical model was first developed using coupling wave equations and the boundary condition method to analyze the characteristics of the device with bending and off-axis deformation under elastic strains. The relationships between the frequency shifts of the SAW device and the bending strain and off-axis angle were obtained, and the results were identical to those from the theoretical calculations. Finally, we performed proof-of-concept demonstrations of its multisensing potential by monitoring human wrist movements at various off-axis angles and detecting UV light intensities on a curved surface, thus paving the way for the application of versatile flexible electronics.